2013
DOI: 10.1038/srep03148
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and polymorphisms in AR, DAT1, DRD2 and COMT genes in Datoga pastoralists of Tanzania

Abstract: The aim of this study was to analyse the relationships between polymorphisms in four candidate genes (AR, DAT1, DRD2, and COMT) and aggression in men from a traditional society of East African pastoralists, the Datoga. Buss and Perry's Aggression Questionnaire was used to measure aggression. The number of CAG repeats in the AR gene was negatively correlated with physical aggression, anger, and hostility. Among the genes of the dopaminergic system, a significant single-gene effect was detected only for DRD2 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 51 publications
4
22
0
4
Order By: Relevance
“…DRD2 rs4648317 was found to be associated with Dr-l in women only, which chimes with recent findings of female-specific associations between Dr-l and the need for power, an implicit motivation relevant to sociosexuality [17]. Moreover, this dopamine receptor gene association echoes the relationship between 2D:4D and DRD4 found in Hadza men [10]. Although intriguing, replication of these findings is needed, given firstly, that they did not survive correction for multiple comparisons, and secondly, these SNPs were not identified in the largest study to date [9].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…DRD2 rs4648317 was found to be associated with Dr-l in women only, which chimes with recent findings of female-specific associations between Dr-l and the need for power, an implicit motivation relevant to sociosexuality [17]. Moreover, this dopamine receptor gene association echoes the relationship between 2D:4D and DRD4 found in Hadza men [10]. Although intriguing, replication of these findings is needed, given firstly, that they did not survive correction for multiple comparisons, and secondly, these SNPs were not identified in the largest study to date [9].…”
Section: Discussionsupporting
confidence: 84%
“…We found that AR rs6152 is significantly associated with lefthand (supporting [10,15,16]), but not right-hand 2D:4D (contra [5]). On closer inspection, we found that this held in women only, echoing [16].…”
Section: Discussionmentioning
confidence: 65%
“…Our data show that aggression and dominance was indeed highest in Datoga men, and this was also reflected in the reported history of fights with same sex peers. Previous studies demonstrated that self-ratings in physical aggression were negatively and significantly associated with the number of CAG repeats of the AR gene in Datoga men (Butovskaya et al, 2013b), but such association was found to be absent in Hadza men (Butovskaya et al, 2010b). This suggests that ethnic differences in male aggression may be attributable-at least in part-to genetic differences moderating androgen expression and its effect on aggression.…”
Section: Discussionmentioning
confidence: 88%
“…The AQ is comprised of 29 statements, grouped into four subscales: physical aggression (nine items), verbal aggression (five items), anger (seven items), and hostility (eight items). This instrument was initially translated by us into Kiswahili and adjusted to local conditions following standard procedures in crosscultural research (translation and back-translation by four bilingual assistants; see Butovskaya et al, 2010bButovskaya et al, , 2013b for the use in previous studies). In the present study, Cronbach's alphas for the AQ subscales in the Hadza ranged from 0.60 to 0.63, and in the Datoga from 0.53 to 0.63.…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%
“…This limited study found no significant association with polymorphic regions of this gene and aggressive tendencies, in agreement with other findings (Hemmings, 2012). Drawing once again from better studied species, polymorphic variants at a range of additional gene targets (including the D2 dopamine receptor [DRD2] locus) have been identified as contributory to hyper aggression (Butovskaya et al, 2013), and thus the search for equine gene targets should undoubtedly be widened accordingly, preferably via GWAS.…”
Section: Genomic Predictors Of Aggressionmentioning
confidence: 99%